Imperial Refugee Management : Moving Greek Refugees Through the British Empire and into the Belgian Congo (1942–1945) - Lingelbach, Jochen (The Journal of Imperial and Commonwealth History, 2022)
During the Second World War, 2,700 Greek refugees lived in camps in Eastern Belgian Congo and Ruanda-Urundi. They had escaped from the German Nazi occupation and famine conditions on the Aegean Islands. Their movement through Turkey, Syria, Palestine, Egypt, Kenya, Tanganyika and Uganda was part of a more extensive network of refugee hosting and transfer, orchestrated by British officials in Cairo and guided by strategic interests in London. This article uncovers this overlooked episode and situates it in the broader history of the thousands of European refugees who found refuge in the Middle East and Africa. It argues that this was part of a more extensive system of imperial refugee management with implications for the history of the British Empire and the international refugee regime. Adding to the historiography of the empire’s war effort, it uncovers the contribution of Africans to hosting distressed European refugees. It further highlights the importance of imperial rule in the emergence of the post-war international refugee regime. Due to the racism of the colonial division of labour and society, European refugees in Africa enjoyed a comparably comfortable situation. The imperial refugee regime cared well for its white subjects, housing them in some of the most privileged refugee camps of the world.